Sponge spicules indicate Holocene environmental changes on the Nabileque River floodplain, southern Pantanal, Brazil - Kuerten, Sidney; Parolin, Mauro; Assine, Mario L. [UNESP]; McGlue, Michael M. (Springer Nature, 2013)
Sponge spicules are siliceous microfossils that are especially useful for analysis of sandy fluvio-lacustrine sediments. Sponge spicules in a long sediment core (~550 cm below surface), consisting of fine sand, sandy silt, and organic-rich mud, recovered from the floodplain of the Nabileque River, southern Pantanal, Brazil (S20°16′38. 3″/W57°33′00. 0″), form the basis of a novel paleoenvironmental interpretation for this region. Optically stimulated luminescence dates constrain the timing of deposition to the middle-late Holocene and all spicules identified are typical of the Brazilian cerrado biome. The base of the section is dominated by Oncosclera navicella Carter 1881, Metaniaspinata Carter 1881, and Corvospongilla seckti Bonetto and Ezcurra de Drago 1966, which indicate a lotic to semi-lotic environment strongly influenced by an actively meandering river channel at ~6. 7-5. 7 ka BP. The appearance of Heterorotula fistula Volkmer-Ribeiro and Motta 1995, Dosilia pydanieli Volkmer-Ribeiro 1992 and Radiospongilla amazonensis Volkmer-Ribeiro and Maciel 1983 at ~340 cm downcore suggests a reduction in flowing water and a more stable lentic environment, consistent with deposition in an oxbow lake. This oxbow lake environment existed during an interval of regional aridity between ~4. 5 and 3. 9 ka BP. Spicules, as well as phytoliths and diatoms, are highly variable moving up-section, with species from both lotic and lentic ecosystems present. Above ~193 cm, the total abundance of spicules declines, consistent with wetter climate conditions and development of an underfit river similar to the modern floodplain. Results support hypotheses related to migration of the Paraguay River inferred from geomorphological studies and add a key southern-region dataset to the emerging Holocene database of paleoenvironmental records from the Pantanal wetlands. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Floodplain lakes; Fluvial sediments; Holocene; Nabileque River; Pantanal; Sponge spicules; alluvial deposit; biome; cerrado; climate variation; floodplain; fluviolacustrine deposit; lentic environment; lotic environment; luminescence; meander; microfossil; oxbow lake; paleoenvironment; river channel; sediment core; sponge; Brazil; Bacillariophyta; Corvospongilla; Dosilia; Fistula; Heterorotula; Navicella; Oncosclera